Almost Automorphic Random Functions in Probability - Hui-Sheng Ding; Chao Deng; Gaston M. N’Guérékata (Abstract and Applied Analysis)
We introduce the notion of almost automorphic random functions in probability. Some basic and fundamental properties of such functions are established.